2005
DOI: 10.1126/science.1109676
|View full text |Cite
|
Sign up to set email alerts
|

Parallel and Serial Neural Mechanisms for Visual Search in Macaque Area V4

Abstract: To find a target object in a crowded scene, a face in a crowd for example, the visual system might turn the neural representation of each object on and off in a serial fashion, testing each representation against a template of the target item. Alternatively, it might allow the processing of all objects in parallel but bias activity in favor of those neurons that represent critical features of the target, until the target emerges from the background. To test these possibilities, we recorded neurons in area V4 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

52
497
5
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 608 publications
(573 citation statements)
references
References 25 publications
52
497
5
5
Order By: Relevance
“…Here, as in many other studies (2,5,6), we found that the population of V4 neurons, and many single neurons did indeed give enhanced responses to the search targets compared with the distractors. Like neurons in LIP, V4 neurons become selective roughly 50 ms after the beginning of the visual response to the appearance of the search array.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Here, as in many other studies (2,5,6), we found that the population of V4 neurons, and many single neurons did indeed give enhanced responses to the search targets compared with the distractors. Like neurons in LIP, V4 neurons become selective roughly 50 ms after the beginning of the visual response to the appearance of the search array.…”
supporting
confidence: 69%
“…This feature selectivity is usually manifest from the first spike of the response (2) and is assumed to be due to hard wiring in the network and to a certain extent a feed-forward process (3). When an animal searches for a visual target among distractors it is not unreasonable to assume that neurons in the brain will be selective for the search target, and we have recently shown that neurons in the lateral intraparietal area of the monkey (LIP) become selective for the target in a visual search task even when the monkey makes a saccade away from the receptive field (4).…”
mentioning
confidence: 99%
“…Critically, these activity modulations are also elicited in response to stimuli at task-irrelevant unattended locations (Figure 3b), suggesting that feature-based attention is a spatially global phenomenon. During search for colour-or shape-defined target objects, V4 neurons that prefer target-defining features increase their activity when a target object is present in their receptive field, even when monkeys fixate elsewhere, fail to detect the target, and shift gaze to another object [27]. Such observations underline the fact that feature-based attention operates in parallel across the visual field, independent of the current focus of spatial attention.…”
Section: Guidancementioning
confidence: 55%
“…Instead of providing evidence that focal spatial attention is directed independently and simultaneously to targets and partially matching nontarget objects in the same display, the pattern of N2pc results observed in competition trials could in principle also reflect processes at the earlier stage of feature-based attention, which are known to operate in a spatially global fashion (e.g., Martinez-Trujillo & Treue, 2004;Bichot et al, 2005;Serences & Boynton, 2007). However, previous ERP experiments have reported effects of feature-based attention at post-stimulus latencies of 100 ms (Zhang & Luck, 2009) or 140 ms (Hopf, Boelmans, Schoenfeld, Luck, & Heinze, 2004), well before the typical onset of the N2pc component, suggesting that feature-based attention modulates early feedforward stages in the visual processing hierarchy (e.g., Zhang & Luck, 2009).…”
Section: Discussionmentioning
confidence: 99%